2005
DOI: 10.1111/j.1469-7580.2005.00378.x
|View full text |Cite
|
Sign up to set email alerts
|

Palisade endings in extraocular eye muscles revealed by SNAP‐25 immunoreactivity

Abstract: Palisade endings form a cuff of nerve terminals around the tip of muscle fibres. They are found only in extraocular muscles, but no definite evidence for their role in eye movements has been established. Palisade endings have been reported in all species so far investigated except the rat. In this study we demonstrate that antibodies against SNAP-25, the synaptosomal associated protein of 25 kDa, reliably visualize the complete motor, sensory and autonomic innervation of the extraocular muscles in human, monke… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
42
0
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(47 citation statements)
references
References 42 publications
4
42
0
1
Order By: Relevance
“…Palisade endings were assumed to be sensory structures, compensating for a general lack of conventional proprioceptive receptors (muscle spindles) in the extraocular musculature (Billig, Buisseret-Delmas, & Buisseret, 1997; Donaldson, 2000; Ruskell, Kjellevold Haugen, Bruenech, & van der Werf, 2005; Steinbach, 1987; Weir, Knox, & Dutton, 2000). However, palisade endings also show features that correlate with a motor function: for example, they contain vesicles and are immunoreactive for cholinergic markers (Blumer et al, 2009; Eberhorn et al, 2005; Konakci et al, 2005a, 2005b; Lukas et al, 2000). Furthermore, injections of anterograde tracer into the extraocular motor nuclei label palisade endings, indicating the source of these features lies in the MIF motoneuron pools (Lienbacher, Mustari, Ying, Büttner-Ennever, & Horn, 2011; Zimmermann, May, Pastor, Streicher, & Blumer, 2011; Zimmermann et al, 2013).…”
Section: | Discussionmentioning
confidence: 99%
“…Palisade endings were assumed to be sensory structures, compensating for a general lack of conventional proprioceptive receptors (muscle spindles) in the extraocular musculature (Billig, Buisseret-Delmas, & Buisseret, 1997; Donaldson, 2000; Ruskell, Kjellevold Haugen, Bruenech, & van der Werf, 2005; Steinbach, 1987; Weir, Knox, & Dutton, 2000). However, palisade endings also show features that correlate with a motor function: for example, they contain vesicles and are immunoreactive for cholinergic markers (Blumer et al, 2009; Eberhorn et al, 2005; Konakci et al, 2005a, 2005b; Lukas et al, 2000). Furthermore, injections of anterograde tracer into the extraocular motor nuclei label palisade endings, indicating the source of these features lies in the MIF motoneuron pools (Lienbacher, Mustari, Ying, Büttner-Ennever, & Horn, 2011; Zimmermann, May, Pastor, Streicher, & Blumer, 2011; Zimmermann et al, 2013).…”
Section: | Discussionmentioning
confidence: 99%
“…Several studies support a sensory role of this EOM specific organ [1,2,6,8,9,20]. Specifically, fine structure studies demonstrated that all palisade endings, with the exception of rat's [9] and rabbit's [5], established contacts with the tendon [1,3,4,12,19,21]. In Golgi tendon organs, analogous nerve contacts are sensory [23].…”
mentioning
confidence: 99%
“…13,14 Their location at the muscle-tendon junction has placed palisade endings for many years as candidates for providing eye position signals. 7,9,11,15 Their sensory role has been put into question when molecular analyses and neuronal tracing studies have demonstrated that palisade endings are cholinergic and originate from the EOM motor nuclei, most likely from MIF motoneurons.…”
mentioning
confidence: 99%
“…[7][8][9] Palisade endings are regularly present in the EOMs of frontal-eyed species (human, monkey, cat, dog, and ferret) but infrequent in lateral-eyed species (i.e., they are present in ungulates [pig, cow, horse, and sheep] and rabbit), but absent in most rodents. [10][11][12] Palisade endings are located at the myotendinous junction and formed by nerve fibers that come in from the muscle and extend into the tendon. There, axons make a u-shaped turn, branch, and establish terminal varicosities at the tendon level and around single muscle fiber tips.…”
mentioning
confidence: 99%